Oral Care Protocol and the Prevention of Ventilator-Associated Pneumonia in ICU Patients: A Literature Review - Eppy Setyowati; Bayu Rizky Pratama; Moh Sadli; Intan Cahyanti Sugianto (Indonesian Journal of Global Health Research, 2026)
Patients undergoing mechanical ventilation are at high risk of developing infectious complications, particularly Ventilator-Associated Pneumonia (VAP). Structured oral care through the implementation of an oral care protocol plays a critical role in preventing such infections. This study employed a Systematic Literature Review design guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Relevant articles were identified from databases including Google Scholar, Elsevier, ScienceDirect, and ResearchGate. The review focused on articles published within 2020-2025 and relevant to oral care in mechanically ventilated patients. The keywords used in the article search were Ventilator-Associated Pneumonia, Oral Care Protocol, and Mechanical Ventilation. The findings indicate that structured oral care protocols significantly reduce the incidence of VAP. Effective strategies include the use of additional topical agents such as honey, disposable oral care kits, and individualized care approaches based on appropriate assessment tools. Regular training and ICU nursing certification are also key factors in optimizing the implementation of oral care. Moreover, attention to nurse-to-patient ratios contributes to improved care quality. Oral care for ventilated patients should be integrated into hospital Standard Operating Procedures (SOPs) using an evidence-based approach. Institutional support through training, resource provision, and policy development is essential to enhance intervention effectiveness and reduce complications such as VAP.